Neurometabolite Changes in Hyperthyroid Patients Before and After Antithyroid Treatment: An in vivo1H MRS Study - Kumar, Mukesh; Singh, Sadhana; Rana, Poonam; Kumar, Pawan; Sekhri, Tarun; Kanwar, Ratnesh; D’Souza, Maria; Khushu, Subash (Frontiers in Human Neuroscience, 2021)
Purpose: Patients with hyperthyroidism have frequent neuropsychiatric symptoms such as lack of attention, concentration, poor memory, impaired executive functions, depression and anxiety. These neuro-cognitive impairments such as memory, attention and executive functions appear to be associated with dysfunction in brain regions. The present study was conducted to investigate the metabolic changes in the brain sub-cortical regions, i.e., posterior parietal cortex and DLPFC, in patients with hyperthyroidism before and after anti-thyroid treatment using proton magnetic resonance spectroscopy (1H MRS). Materials and Methods: We collected neuropsychological and 1H MRS data from posterior parietal cortex and DLPFC, in both control and hyperthyroid patients. In addition, follow-up data was available for 19 patients treated with carbimazole for 30 weeks. The relative ratios of the neurometabolites were calculated using LCModel. Analysis of Co-Variance (ANCOVA) using Bonferroni correction was performed between healthy controls and hyperthyroid patients, and a paired-t test was applied in patients at baseline and at follow-up. Spearman’s rank order correlation was used to analyse bivariate associations between thyroid hormone levels and metabolite ratios, and the partial correlation analysis was performed between neuropsychological scores and metabolite ratios, with age and sex as covariates, in the patients before and after treatment. Results: Our results revealed a significant decrease in choline/creatine (GPC+PCh/tCr) in both the posterior parietal cortex and DLPFC in hyperthyroid patients, and these changes were reversible after anti-thyroid treatment.The posterior parietal cortex also showed significantly reduced glutamate/creatine (Glu/tCr), Glx/tCr and increased GSH/tCr ratios in the hyperthyroid patients over control subjects. In DLPFC, only NAA+NAAG)/tCr was increased in the hyperthyroid patients.After anti-thyroid treatment, (GPC+PCh)/tCr increased, and Glx/tCr decreased in both brain regions in the patients at follow-up. Interestingly,(GPC+PCh)/tCr in DLPFC showed a significantly inverse correlation with fT3 in hyperthyroid patients at baseline, whereas NAA/tCr showed positive correlations with fT3 and fT4 in hyperthyroid patients before and after anti-thyroid treatment, in the posterior parietal cortex.In DLPFC, only (NAA+NAAG)/tCr showed positive correlations with fT3 and fT4 in the patients before treatment. Conclusion: The overall findings suggest that all the brain metabolite changes were not completely reversed in the hyperthyroid patients after anti-thyroid treatment, even after achieving euthyroidism.